Experimental investigations on combustion characteristics of fuel briquettes made from vegetable market waste and saw dust. (2020) - Afsal, Asna; David, Robin; Baiju, V.; Suhail, N. Muhammed; Parvathy, U.; Rakhi, R.B.
Abstract: The safe and sound disposal of vegetable market waste (VMW) is a major concern of India today. VMW is being produced in millions of tonnes in urban areas, which are often deposited in dumpsites, left untreated, or burned in open fires. A potential remedy for these waste disposal and high fuel dependence on wood as fuel is the conversion of this biomass into high-density briquettes. This paper presents an experimental exploration of fuel properties of bio-briquettes made from a combination of VMW and sawdust (SD). In the present work, binary briquettes have been made from VMW in combination with SD in a ratio of 25, 50, 75, and 100% by weight using bentonite clay as a binder. Furthermore, a comparative study between the VMW based biomass briquettes with firewood, coal, and conventional sawdust briquettes are also included in this study. Raw green vegetable wastes were collected from markets and were kept for open sun drying. The dried matter was then transformed into a pulverized form and eventually converted to briquettes. The percentage of moisture content, percentage volatile matter content, ash content percentage, fixed carbon content, and calorific values of the briquettes were investigated. The results showed that the composite briquettes had improved combustion characteristics like higher calorific value and more volatile matter content compared with pure VMW briquettes. The percentage volatile matter content of VMW briquette enhanced from 71.72% to 83.2% for the composite briquette of VMW and SD with the highest percentage at the proportion 25:75 (VMW: SD). The calorific value of bio-briquettes ranges from 14.002 to 15.721 MJ/kg and the highest heating value was obtained for the composite briquette of VMW and SD with proportion 25:75. Even though lignin contents of vegetable market waste were lesser (3.23–5.51%) compared to other ligno-cellulosic biomass, good quality biomass briquettes were produced.